¿Podemos construir la paz? Perspectivas, ritualidades, encuentros - Arango Calad, Carlos (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2019)
Can we build peace? relaunches the question of peacebuilding as a commitment to research and reflection beyond established theoretical frameworks. Each chapter of this book reflects the search and the questions that mobilize different scholars from their own intellectual trajectories and life experiences. It is a book that harbors the richness of its content in the diversity of methodical approaches to the question of peace. Thus, it understands that to build, to recognize, to dissent, to transform, are verbs of solidarity with which the transition from a country in conflict to a possible peace is conveyed. From the academic point of view, one of the great challenges is to consolidate the convergence of interests, knowledge and actions that allow a clear understanding of the complexity of the problems of the transition to peace. One of the premises that inspires the authors is to propose a decentered reading of established theories, without ignoring their value and without rejecting the necessary specificity required to elucidate and address specific issues such as psychological effects, legal discussions or media logics. Thus, the reader will find dissertations on cardinal issues of social, political and cultural life on which it is necessary to reflect in the processes of overcoming armed conflicts. This proposal seeks to delocalize, from a theoretical and methodological point of view, the research reflection and promote an interdisciplinary dialogue among authors from different regions and countries, in order to summon readers interested in understanding, from different points of view, the tensions, problems and ambiguities that Colombia faces in terms of peace.